Analisis Kualitas Informasi pada Sistem Informasi Akademik (SIA) UIN Sumatera Utara dan Dampaknya pada Kepuasan Mahasiswa - Nabila Shahira; Muhammad Irwan Padli Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to conceptually examine the impact of Information Quality (QI) in the Academic Information System (SIA) of UIN North Sumatra on Student Satisfaction. As the main operational element on campus, SIA relies heavily on the quality of the information it produces to ensure effective services and help students in making academic decisions. This research uses a conceptual literature study approach with the DeLone and McLean (DandM) Information system succes Model framework. The results of the analysis show that Information Quality (QI) has a positive and significant impact on SIA UINSU Student Satisfaction through its four dimensions Accuracy, Timeliness, Relevance, and Completeness. The problem of data inaccuracy (grades) and late updates (schedules) in academic portals is the main issue that causes dissatisfaction, while emphasizing that QI is a key factor in the success of the system. This study concludes that ensuring data quality must be a top priority, and advises SIA managers to focus on procedures that ensure accuracy and timeliness in data input to increase user satisfaction.